Technological Evolution of Architecture, Engineering, Construction, and Structural Health Monitoring of Bridges in Peru: History, Challenges, and Opportunities - Carlos Cacciuttolo; Esteban Muñoz; Andrés Sotil (Applied Sciences)
Peru is one of the most diverse countries from a geographical and climatic point of view, where there are three large ecosystem regions called coast, Sierra, and jungle. These characteristics result in the country having many hydrographic basins, with rivers of significant dimensions in terms of the width and length of the channel. In this sense, there is a permanent need to provide connectivity and promote trade between communities through road bridge infrastructure. Thus, Peru historically developed a road network and bridges during the Inca Empire in the Tawantinsuyu region, building a cobblestone road network and suspension bridges with rope cables made of plant fibers from vegetation called Coya-Ichu. This is how bridges in Peru have evolved to meet contemporary vehicular demands and provide structural stability and functionality throughout their useful life. This article presents the following sections: (a) an introduction to the evolution of bridges, (b) the current typology and inventory of bridges, (c) the characterization of the largest bridges, (d) a discussion on the architecture, engineering, construction, and structural health monitoring (AECSHM) of bridges in the face of climate change, earthquakes, and material degradation, and (e) conclusions. Finally, this article presents opportunities and challenges in terms of Peru’s architecture, engineering, construction, and structural health monitoring of road bridges. Special emphasis is given to the use of technologies from the era of Industry 4.0 to promote the digital construction and structural health monitoring of these infrastructures. Finally, it is concluded that the integration of technologies of sensors, the IoT (Internet of Things), AI (artificial intelligence), UAVs (Unmanned Aerial Vehicles), remote sensing, BIM (Building Information Modeling), and DfMA (Design for Manufacturing and Assembly), among others, will allow for more safe, reliable, durable, productive, cost-effective, sustainable, and resilient bridge infrastructures in Peru in the face of climate change.